Implementation of Driver Drowsiness Alert and Automatic Vehicle Control System Using Arduino - gowda, Akash BR; Bchavda, Dharmesh; ulla, MD Ismail zabi; N, Swetha (International Journal of Computer Sciences and Engineering, 2025)
The model is about making cars more intelligent and interactive which may notify or resist user under unacceptable conditions, they may provide critical information of real time situations to rescue or police or owner himself. Driver fatigue resulting from sleep deprivation or Drunken driving is prevented is an important factor in the increasing number of accidents on today's roads. In this paper, we describe a real -time safety prototype that stop vehicle ignition. The purpose of such a model is to advance a system to detect fatigue symptoms in drivers and control the vehicle to avoid accidents. In this paper, we propose a driver drowsiness detection and alcohol detection system in which alcohol detection sensor and image processing are used for detecting the driver. If the driver is found to have sleep, or driver in an alcoholic condition then buzzer will start and then turns the vehicle ignition off.